ANALISIS PROSES PEMBELAJARAN MATEMATIKA MENGGUNAKAN TRANSCRIPT BASED LEARNING ANALYSIS (TBLA) - Siska Candra Ningsih; Titis Sunanti (EMTEKA: Jurnal Pendidikan Matematika, 2024)
The learning process in the campus environment must be the concern of every lecturer. The learning process must facilitate students to achieve the expected competencies. The aims of this research are (1) to analyze the learning process to find out whether the learning process in the Mathematics Education Study Program is student centered or still lecturer centered; (2) to describe the activities carried out by students during the learning process. The research instrument was a video recording during the learning process which was analyzed using Transcript Based Learning Analysis (TBLA). Based on the results of the analysis, it is known that the learning process in the Mathematics Education Study Program provides presentation opportunities for students who have been divided into several groups to deliver learning material. In this presentation session, learning was student centered. Students looked active, conversations were dominated by students, and there was reciprocal discussion between the group of students presenting and other students. The next session is a group discussion session. In this session there was interaction between lecturers and students, but the lecturer seemed more dominant because he had to answer questions from students from several groups who did not understand the worksheets given. Students are seen asking and responding to questions from the lecturer.